Photoprotective effect of mycosporine-like aminoacids extracts on natamycin, saffron carotenoids and epigallocatechin gallate in acidified beverages exposed to different light sources - Teixeira, Gustavo Henrique de Almeida [UNESP]; Morelli, Luiza; Ma, Sihui; Stewart, Amanda; O'Keefe, Sean Francis (Oxford University Press (OUP), 2019)
Natamycin has been used as a natural food additive to control the growth of many microorganisms. However, this polyene is very sensitive to light exposure. Therefore, the objective of this study was to evaluate the photoprotective effect of mycosporine-like aminoacids (MAA) in acidified beverages containing natamycin, epigallocatechin gallate (EGCG), and saffron carotenoids (SC) stored in three conditions: fluorescent, low and high intensity Light-Emitting Diode (LED) light. Crude MAA extract addition resulted in faster degradation of natamycin, EGCG, and SG. Even in the presence of EDTA-Na, there was higher degradation of natamycin in the presence of MAA extracts. Purification of the MAA extracts using solid-phase extraction (SPE) resulted in slight, but significantly better retention of natamycin under fluorescent and low LED lighting; this was not seen at high LED, however. Therefore, purified MAA extract expressed a potential photoprotective effect on natamycin in acidified beverages.
Keywords: Epigallocatechin gallate; fluorescent light; high performance liquid chromatography with diode-array detection; high-performance liquid chromatography with mass spectrometry; light emitting diode; Palmaria palmata L